2012
DOI: 10.1124/jpet.111.186908
|View full text |Cite
|
Sign up to set email alerts
|

P-Glycoprotein (ABCB1) and Breast Cancer Resistance Protein (ABCG2) Restrict Brain Accumulation of the Active Sunitinib MetaboliteN-Desethyl Sunitinib

Abstract: N-desethyl sunitinib is a major and pharmacologically active metabolite of the tyrosine kinase inhibitor and anticancer drug sunitinib. Because the combination of N-desethyl sunitinib and sunitinib represents total active drug exposure, we investigated the impact of several multidrug efflux transporters on plasma pharmacokinetics and brain accumulation of N-desethyl sunitinib after sunitinib administration to wild-type and transporter knockout mice. In vitro, N-desethyl sunitinib was a good transport substrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…We found that absence of Abcb1a/1b and Abcg2 does not affect oral availability, but does influence brain and testis accumulation of regorafenib. Similar effects have been described previously for example with sorafenib, sunitinib and CYT387 (14,28,33). Additionally, we found a significant detectable impact of single Abcb1a/1b knockout on the regorafenib accumulation in the testis, while there was a slight but insignificant impact of Abcb1a/1b absence in the brain.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We found that absence of Abcb1a/1b and Abcg2 does not affect oral availability, but does influence brain and testis accumulation of regorafenib. Similar effects have been described previously for example with sorafenib, sunitinib and CYT387 (14,28,33). Additionally, we found a significant detectable impact of single Abcb1a/1b knockout on the regorafenib accumulation in the testis, while there was a slight but insignificant impact of Abcb1a/1b absence in the brain.…”
Section: Discussionsupporting
confidence: 89%
“…We think that our findings can be a good source for future clinical studies of cancer patients with CNS involvement, as we here showed a clear impact of ABCB1 and ABCG2 in restricting brain penetration of regorafenib. Moreover, based on our previous experience (14,20,28), we suggest that combined administration of regorafenib with ABCB1 and ABCG2 inhibitors such as elacridar might improve the brain concentration and thus efficacy of regorafenib against metastases located behind an intact BBB.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The pharmacokinetic role of ABCG2 and ABCB1 was also shown using Abcg2 −/− , Abcb1a/1b −/− and Abcg2 −/− /Abcb1a/1b −/− mice Tang et al, 2012Tang et al, , 2013. For example, we demonstrated that the maximum concentration and AUC 0-4 of sunitinib were significantly higher in Abcg2 −/− , Abcb1a/1b −/− and Abcg2 −/− /Abcb1a/1b −/− mice than in wild-type ones when sunitinib was given orally, but not intraperitoneally .…”
Section: Sunitinibmentioning
confidence: 99%
“…83 According to the same line of evidence, MRP4 (ABCC4) and BCRP (ABCG2) are also mainly localized in the apical/luminal membrane of brain endothelial cells (Figure 2). 35,84 . Density-gradient centrifugation of membranes By using density-gradient centrifugation brain capillary membranes can be fractionated to obtain purified preparations of apical/luminal and basolateral/abluminal membranes.…”
Section: Functional Assaysmentioning
confidence: 99%